Exploring local communities’ perceptions of protected area authorities: a case study from Khlong Lan National Park and Mae Wong National Park in Thailand - Phoonjampa, Rungnapa; Srirattanaporn, Surasak; Phumanee, Worrapan; Pierrefeu, Capucine; Singh, Rohit; Ong, Elliott James (Frontiers in Conservation Science, 2023)
Community-rangers relations play a critical role in conservation and can significantly affect the efficacy of Protected Areas (PAs). However, their dynamic has long been overlooked. This study assesses the relationship between communities and PA authorities in 39 villages adjacent to two National Parks in Thailand. Using the responses of 200 participants gathered through a Likert-type survey questionnaire, we analyzed community perception using Ordinal Logistic Regression models. Results indicate good community-ranger relations in the study area. Specifically, we found that regular communication and community involvement in decision-making significantly impact trust and respect towards PA authorities. The models further reveal that while education levels influence trust, a culture of respect for authority figures remains deeply rooted in local communities, highlighting the importance of PA authorities' engagement with communities. Our results suggest that capacity building for field staff, in particular social skills and collaboration with local communities, has the potential to improve the relation between communities and rangers. As global efforts intensify to achieve target 3 of the Post-2020 Global Biodiversity Framework, this research offers valuable insights into fostering respectful and trusting relations between communities and PA authorities.